Mandates are not enough: placement provider and systems factors that drive ambulatory healthcare use for children in foster care - Sarah J. Beal; Adam C. Carle; Constance A. Mara; Courtney B. Dunn; Katie Fox; Mary V. Greiner (Frontiers in Pediatrics, 2026)
Introduction In the United States, children are mandated to receive healthcare when they enter foster care and regularly thereafter; states may require more frequent visits. Despite regulations and public insurance to support access to healthcare for young people in foster care, health outcomes for this population remain poor. This study seeks to understand the extent to which caregiver/placement characteristics, child characteristics, and an information-sharing intervention are associated with receipt of mandated healthcare visits for youth in foster care, which may help the field to better understand why health disparities persist for youth in foster care. Methods This retrospective observational study uses administrative data from the child welfare system linked to the electronic health record at a freestanding children's hospital that is contracted to provide mandated healthcare visits for children entering foster care or experiencing placement changes. All children (0–21 years) in foster care for at least one day in a licensed, kinship, group home, or independent living placement in a single Ohio county between 2012 and 2025 ( N = 24,904 placements for N = 10,729 youth) were included. Cross-classified multilevel logistic models predicted mandated visits within placements and accounted for the cross-classification of children within families of origin, placement providers, and the clustering of repeated observations within children. Results The odds of completing a mandated visit was 73%. Placement providers accounted for the largest amount of variance in receipt of mandated care (44% in the adjusted model). Placement in settings other than licensed foster homes (i.e., kinship, group home, independent living) significantly reduced the likelihood of visits. While prior placement providers' experience was generally beneficial, it did not increase visit completion among those in kinship care. Across child characteristics (e.g., age in years, sex, race, ethnicity, number of unique medical diagnoses, number of unique mental health diagnoses), mental health diagnoses were significantly and meaningfully associated with completed visits. Finally, information sharing between healthcare and child welfare systems was associated with a greater likelihood of completing mandated visits (OR = 1.50). Discussion These results indicate that simply mandating visits is insufficient to ensure their completion. Caregiver factors, information sharing between healthcare and child welfare systems, and children's needs likely all represent mechanisms by which the healthcare and child welfare systems can increase mandated healthcare use.